Effect of partial grapevine defoliation (vitis vinifera) on wine quality / efecto de la defoliación parcial en uva (vitis vinifera) sobre la calidad del vino (2013)
The wine quality was determined for partially-defoliatedgrapevines grown in Villa de Leyva, Colombia at an elevation of2,143 masl. The experimental design was totally randomized,with two treatments (50% defoliation and 0% defoliation) andthree repetitions per treatment. The planting material consistedof five-year-old vines of Vitis vinifera cv. Chardonnay, trainedto trellises, with a spacing of 2.1 m x 1 m. Every fifteen days,the plants in the defoliation treatment underwent the removalof half of the newly-emerged leaves. Before undertaking themicro-vinification process, the total soluble solids (TSS) weremeasured in the grape must, and after a fermentation of 100days, wine quality parameters were measured, namely: residual sugars (TSS of the wine), pH, total titratable acid (TTA), and potential alcohol content of the wine. In the plants undergoing partial defoliation, the total soluble solids in the grape must increased, as well as the wine pH and potential alcohol content. At the same time, total titratable acid decreased in the wine of partially-defoliated plants. These results demonstrate that the wine quality was greatly improved by the reduction of leaf area in Chardonnay variety grape plants. / Con el uso de un diseño completamente aleatorizado, con dos tratamientos (defoliación al 50% y sin defoliación parcial) y tres repeticiones por tratamiento, se determinó la calidad del vino en plantas de uva sometidas a defoliación parcial temprana en Villa de Leyva – Colombia a una altitud de 2.143 msnm. Como material vegetal se utilizaron plantas de Vitis vinifera L. cv. Chardonnay de cinco años de edad, sembradas en un sistema de espalderas a 2,1 x 1 m. Quincenalmente, se realizó la defoliación parcial a las plantas, la cual consistió en retirar una de cada doshojas recién emergidas en cada una de las plantas sometidas al tratamiento de defoliación. Antes de iniciar el proceso de microvinificación se determinaron los sólidos solubles totales (SST) del mosto, y posterior a la fermentación alcohólica, la cual tuvo una duración de 100 d, se determinaron los parámetros de calidad del vino, como: azucares residuales (SST del vino), pH, acidez total titulable (ATT) y contenido potencial de alcohol del vino. Se encontró un aumento en los SST del mosto, el pH y el contenido potencial de alcohol del vino procedente de las plantas defoliadas. A su vez, la ATT del mismo disminuyó en las plantas defoliadas. Estos resultados demuestran que la calidad del vinose vio favorecida fuertemente por la disminución del área foliar en plantas de uva cv. Chardonnay.